Prospects for the formation of an investment and legal regime of digital objects in the legislation of the EAEU countries - Kamenkov, Viktor S.; Kunitskaya, Olga M. (Journal of the Belarusian State University. Law, 2026)
This article provides a general overview of the legal framework for the creation and circulation of digital assets, developed in accordance with the public policies of the EAEU member states (using Belarus, Russia, and Kazakhstan as examples). It is determined that despite social and political differences between countries, digital economy concepts, including the use of distributed ledger technology, have become among the most important factors driving social development. It is revealed that the task of effectively developing a legal framework for the creation and circulation of digital assets cannot be achieved without considering the technical nature of the digital token itself, asset tokenisation, and a well-developed investment theory. The article also outlines prospects for the development of digital investments, the legal nature and legal regime of which remain to be determined. It is established that the institutionalisation of digital investments is based on the political framework for their legal support, including in the context of the development and harmonisation of legislation in the EAEU member states. Successful legal support for the implementation and development of digital technologies will lead to a more favourable investment climate.
Keywords: digital economy; digital token; tokenisation; investments; investment implementation; legal regime of digital investments